2016
DOI: 10.1111/sjop.12324
|View full text |Cite
|
Sign up to set email alerts
|

Parental socioeconomic status and child intellectual functioning in a Norwegian sample

Abstract: . (2016). Parental socioeconomic status and child intellectual functioning in a Norwegian sample. Scandinavian Journal of Psychology, 57, 399-405.Socioeconomic status (SES) in childhood has been linked to cognitive function and future academic and occupational success in studies from several countries. However, previous Nordic studies have shown inconsistent results regarding the strength of this link. We therefore investigated the association between SES and cognitive functioning in a sample of 255 Norwegian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
15
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 53 publications
5
15
0
3
Order By: Relevance
“…The importance of taking cultural differences in socio-economic status into account is illustrated in studies of intellectual function. For example, the effect of socio-economic status on intellectual function is much weaker in samples from Nordic countries than in U.S. samples ( Andersson et al, 1996 ; Osler et al, 2013 ; Ellertsen et al, 2016 ).…”
Section: Discussionmentioning
confidence: 95%
“…The importance of taking cultural differences in socio-economic status into account is illustrated in studies of intellectual function. For example, the effect of socio-economic status on intellectual function is much weaker in samples from Nordic countries than in U.S. samples ( Andersson et al, 1996 ; Osler et al, 2013 ; Ellertsen et al, 2016 ).…”
Section: Discussionmentioning
confidence: 95%
“…This probably reflects both the instability of inattentive behaviour and the large number of co-existing and new challenges influencing a child through childhood and adolescence. Previous studies have for example shown the importance of socio-economic factors in general (e.g., [ 26 ]), with some cultural differences regarding the importance of its subcomponents [ 27 ] and consequences [ 28 ]. Further studies should thus include a larger number of predictors and a more diverse sample than in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Las debilidades más frecuentemente mencionadas, como la presencia de elementos desactualizados, son esperables considerando la cada vez más rápida obsolescencia de los instrumentos, atendida la velocidad de los cambios tecnológicos y culturales (ITC, 2013). Por otra parte, la percepción de los profesionales de los sesgos hacia grupos específicos, como niños de sectores rurales o vulnerables económicamente, son una crítica frecuente a las escalas Wechsler en cuanto a la carga cultural que presentan, especialmente en las subpruebas verbales, que favorecen a niños de nivel educacional más alto (Cianci et al, 2013;Eilertsen et al, 2016;Fuica et al, 2014). Este último aspecto se constituye en un desafío para los psicólogos en la evaluación de esta población y sugiere la necesidad de utilizar otros instrumentos y/o fuentes de información para compensar estas falencias.…”
Section: Discussionunclassified